Simultaneous realization of structure manipulation and emission enhancement in NaLuF4 upconversion crystals. Issue 44 (27th October 2015) - Lin, Hao; Xu, Dekang; Li, Anming; Teng, Dongdong; Yang, Shenghong; Zhang, Yueli
Abstract : The enhanced upconversion emission in NaLuF4 :Yb 3+, Er 3+, Tm 3+ nano/micro-crystals through Gd 3+ doping. Abstract : Gd 3+ doped NaLuF4 :Yb 3+, Er 3+, Tm 3+ nano/micro-crystals with the enhanced upconversion (UC) emission were successfully prepared through a hydrothermal method with the assistance of citric acid. As for Gd 3+ doped α-NaLuF4, before the phase transformation (when Gd 3+ content ≤40 mol%), UC luminescence intensities in the red region from α-NaLuF4 :Yb 3+, Er 3+, Tm 3+ nanocrystals doped with 40 mol% Gd 3+ are enhanced by 13 times compared to the Gd 3+ -free sample. As for Gd 3+ doped α/β-mixed NaLuF4, with the increase of Gd 3+ content, the crystal structure transforms from the α/β-mixture to a pure hexagonal phase without a long reaction time or a high reaction temperature. Red UC emissions from NaLuF4 :Yb 3+, Er 3+, Tm 3+ crystals with 60 mol% Gd 3+ doping are enhanced by 9 times. The mechanisms of the enhanced UC emission and phase transformation by introducing Gd 3+ are discussed in detail. Furthermore, in order to obtain various structures of NaLuF4 nano/micro-crystals before Gd 3+ doping and demonstrate the advantages of Gd 3+ doping, the effects of NaF content, reaction time and temperature on the crystal structure of Gd 3+ -absent NaLuF4 crystals are systematically studied. The results suggest that the intense red UC luminescence from Gd 3+ doped NaLuF4 :Yb 3+, Er 3+, Tm 3+ nano/micro-crystals may have potential applications in biological imaging and optoelectronic devices.